Pengaruh Isometric Handgrip Exercise terhadap Tekanan Darah pada Penderita Hipertensi di Padukuhan Papringan Catur Tunggal Depok Sleman Yogyakarta - Ririn ambarita, Ririn Ambarita; Rina, Fransisca Anjar; CB, Suparmi (Caring : Jurnal Keperawatan, 2025)
Hypertension is one of the leading causes of death due to non-communicable diseases. Uncontrolled hypertension can lead to various complications, making effective management essential. One effective non-pharmacological intervention is the isometric handgrip exercise, which involves sustained muscle contractions without changing muscle length and has been shown to reduce systolic and diastolic blood pressure. This study aims to determine the effect of isometric handgrip exercise on blood pressure in individuals with hypertension. The study was conducted over five consecutive days from December 27 to 31 in Padukuhan Papringan, Caturtunggal, Depok, Sleman, Yogyakarta. A pre-experimental design with a one-group pretest-posttest method was used. A purposive sampling technique was employed, involving 33 hypertensive individuals aged 44–64 years. Data were collected using observation sheets and a standard operating procedure (SOP) guide for the isometric handgrip exercise, which participants followed independently at home. The data were analyzed using the Wilcoxon test. The results showed a significant difference in systolic blood pressure before and after the intervention (p = 0.000), but no significant difference in diastolic blood pressure (p = 0.580). These findings suggest that isometric handgrip exercise can be an effective method for reducing systolic blood pressure in hypertensive patients. Future research is recommended to ensure consistency in exercise using tools like the Muscle Strength Testing (MMST) and to implement controlled supervision during the intervention for optimal exercise accuracy.